Analysis of Factors that Affect Customer Satisfaction, Customer Loyalty at Manado Advent Hospital with a Servqual Approach - Ronny H. Walean; Leonard Stiefen Mumek (Pusat Riset dan Inovasi Nasional, 2025)
In meeting the basic needs of society, public services are important, especially in the health sector. A health institution, Manado Advent Hospital, was the focus of this research. With the vision of making Manado Advent Hospital the main choice for the people of North Sulawesi province and its surroundings and becoming the right hand of evangelism. The aim of this quantitative research is to analyze the quality of health services at the Manado Advent Hospital using the servqual method (physical evidence, reliability, responsiveness, trust and empathy). Apart from that, this can be used as evaluation material for management to improve service quality. Researchers have 11 hypotheses with a sample size of 208 through a questionnaire distributed in October 2024. The data can be analyzed using the Structural Equation Model (SEM) assisted by the SmartPLS statistical program. The results of the five variables in service quality found that there was one variable, namely assurance (H4), which did not have a significant and positive effect on customer satisfaction. Likewise with hypotheses H6, H7, H8, H9 which do not have a positive and significant effect on customer loyalty. rather, an indirect impact can be seen in variables H1, H2, H3 and H5 where these four variables have a positive and significant impact after the customer satisfaction variable (H11) acts as a mediator that influences customer loyalty. The population in this study were patients seeking treatment at this hospital. This is different from previous research which only examined outpatients. This research was carried out on inpatients who used BPJS insurance.